TEACHERS' SELF-ASSESSMENT OF THE COMPETENCIES OF LEARNING TO LEARN AND REFLECTION IN THE CONTEXT OF SCHOOL AS A LEARNING ORGANIZATION - Bubnys, Remigijus; Pilkienė, Greta; Gudinavičius, Benas (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
This article analyses teachers' self-assessment of the competencies of learning to learn and reflection in the context of school as a learning organization. The survey in the form of a written questionnaire was performed and 141 teachers of the city of Vilnius have participated in it. The research reveals the self-assessment results of the skills in the field of time evaluation, planning and management; information search, perception, systematization and adaptation; communication and cooperation in group; and reflection. Teachers highlight the sufficiency of the time distribution for tasks and deadlines skills; awareness and lower level skills of systematization of the information; skills of reception of comments from the members of the group, their consideration or the listening and understanding of the views of the members; skills of abstract conceptualization, which are related to drawing conclusions and anticipating ideas for the future.